Language and politics in Pakistan - Rahman, Tariq (New Delhi, 1996)
Language and Politics in Pakistan is a study of the links between language, politics and ethnicity in Pakistan. Rahman reviews the history of all the major ethnic and language movements that have occurred and still continue in Pakistan today, such as the Bengali, Sindhi, Pashto and Punjabi movements. In addition, he also discusses smaller scale movements. This book is a very important contribution to the post-Independence history of Pakistan and by extension to the specific social configurations of the Indian subcontinent.
Keywords: Sociolinguistics-Pakistan